Evaluation of the Scientific Music Effect on Biochemisry Education - Aeen Sharifi (Babol University of Medical Sciences, 2016)
BACKGROUND AND OBJECTIVE: Music can be used in education of some fields such as: Biochemistry and Related fieldsofmolecular Biology. The question that arises here is whether the sequence, number and variety of proteins constituents could be presented via music? Our purpose has been to design and compose of music for proteins and more familiarizing the students with the first structure of them by composed music and evaluation of its role in learning the proteins structure.